Cytological and molecular characterization for ploidy determination in yams (Dioscorea spp.) - Gatarira, C.; Sladekova, L.; Nemeckova, A.; Simonikova, D.; Paliwal, R.; Asfaw, A.; Abberton, Michael T.; Gueye, B.; Asiedu, R.; Cizkova, J.; Hribova, E.; Dolezel, J.; et al. (MDPI, 2021)
Yam (Dioscorea spp.) is a monocotyledonous herbaceous vine plant grown in the tropics and subtropics. It is a multi-species plant with varied intra- and interspecific ploidy levels. Of the 600 species, 11 are cultivated supporting the livelihood of over 300 million people. The paucity of information on ploidy and the genomic constitution is a significant challenge to the crop’s genetic improvement through crossbreeding. The objective of this study was to investigate the ploidy levels of 236 accessions across six cultivated and two wild species using chromosome counting, flow cytometry and genotyping-based ploidy determination methods. Results obtained from chromosome counting and genotyping-based ploidy determination were in agreement. In majority of the accessions, chromosome counting and flow cytometry were congruent, allowing future rapid screening of ploidy levels using flow cytometry. Among cultivated accessions, 168 (71%) were diploid, 50 (21%) were triploid, and 12 (5%) were tetraploid. Two wild species included in the study were diploids. Resolution of ploidy level in yams offers opportunities for implementing successful breeding programmes through intra- and interspecific hybridization.